PENGUJIAN TAN Î´ PADA KABEL TEGANGAN MENENGAH - Syakur, Abdul; Susilowati, Galuh; AK, Satyagraha; Siregar, A. Parlindungan (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
High voltage testing have purpose to investigate the electrical properties of dielectric related with isolation quality of power equipment during pre-installed or in operation time to prevent equipment losses. Isolation quality is important rule to determine electrical equipment quality, especially for power transmission and distribution. Cable, one of this electrical equipment will be investigated in this research using the high voltage testing with the tan Î´ method. We use the high voltage laboratory of PT. PLN (Persero) Pusat Penelitian dan Pengembangan Ketenagalistrikan, Jakarta, for that kind of testing. There are 6 different middle voltage cable types under the test, as the result the measured tan Î´ values not extend the maximum value, as IEC 60502-2 (2005-2) standard, 40 (x10-4), for each cable. According to that measurement, all of six cable types passed the tan Î´ test. Keywords: tan Î´ testing, cable, isolation quality